THE MICROPHONE ARRAY MULTI DOMAIN FUSIONS LOCATION ARITHMETIC - Changjian Deng (International Journal of Research Science and Management, 2018)
To solve the problem that the location accurate is hard to hold under the environment of noise and interfere when using Generalized cross correlation algorithm in microphone array, the paper approaches a delay estimation arithmetic based on multi domain fusions fuzzy recognize. Cross correlation or generalized cross correlation algorithm cannot eliminate the delay calculation error in principle, so the paper combines with characteristics of the time-frequency fault signal and fisher information matrix, adopts the location arithmetic of multi domain fuzzy recognize and phase lock cross correlation, then improves the robustness and accurate of location calculation in Spherical microphone array, and the Numerical simulation results prove the validation of arithmetic